Interplay Between Peripheral and Central Inflammation in Autism Spectrum Disorders: Possible Nutritional and Therapeutic Strategies - Cristiano, Claudia; Lama, Adriano; Lembo, Francesca; Mollica, Maria P.; Calignano, Antonio; Mattace Raso, Giuseppina (Frontiers in Physiology, 2018)
Pre- and post-natal factors can affect brain development and function, impacting health outcomes with particular relevance to neurodevelopmental diseases, such as autism spectrum disorders (ASDs). Maternal obesity and its associated complications have been related to the increased risk of ASDs in offspring. Indeed, animals exposed to maternal obesity or high fat diets are prone to social communication impairment and repetitive behavior, the hallmarks of autism. During development, fatty acids and sugars, as well as satiety hormones, like insulin and leptin, and inflammatory factors related to obesity-induced low grade inflammation, could play a role in the impairment of neuroendocrine system and brain neuronal circuits regulating behavior in offspring. On the other side, post-natal factors, such as mode of delivery, stress, diet, or antibiotic treatment are associated to a modification of gut microbiota composition, perturbing microbiota-gut-brain axis. Indeed, the interplay between the gastrointestinal tract and the central nervous system not only occurs through neural, hormonal, and immune pathways, but also through microbe-derived metabolic products. The modification of unhealthy perinatal and postnatal environment, manipulation of gut microbiota, nutritional, and dietary interventions could represent possible strategies in preventing or limiting ASDs, through targeting inflammatory process and gut microbiota.